STRATEGI CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN AKUNTANSI BIAYA - Nurkhin, Ahmad (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
The problem of the study was how to improve the learning quality at bilingual class for Cost Accounting subject through Content and Language Integrated Learning (CLIL) strategy? It was an action research as a tool to test the effectiveness of CLIL learning strategy at bilingual classes for Cost Accounting subject. The classroom action research was implemented by two (2) cycles and done at bilingual classroom for Cost Accounting 2 subject. The data were collected from the pre-test and post-test which reflected students’ understanding on the materials presented. The indicator of the success was at least 75% students can achieve the complete learning outcome, i.e. 71. The data were collected by observation sheets to obtain the feedbacks from lecturers and students. The results showed that the lecturing implementation of Cost Accounting 2 with CLIL strategy was more qualified and varied technical lectures each meeting. The students’ methods and learning activities were hot seat game, role as a teacher, discuss in pairs, and peer tutoring learning. Furthermore; there were other learning activities such as making a note, preparing resumes formula, updating facebook status, and making a question. Students’ activeness was better than the previous lectures. The success indicators of implementation of the action research can be achieved, 100% students were able to achieve complete learning outcomes value, i.e. 71. The observations also showed that students can improve their teamwork, confidence, and other characters.